Two stations due South of a leaning tower which leans towards the North, are at distances a and b from its foot. If $\alpha $ and $\beta $ are the elevations of the top of the tower from these stations, then prove that its inclination $\theta $ to the horizontal is given by
$\cot \theta = \dfrac{{b\cot \alpha - a\cot \beta }}{{b - a}}$
Answer
Verified
472.8k+ views
Hint:
First draw the diagram carefully with observation of the question. Then we can see three right angled triangles. Assume the unknown lengths with some variables. Apply suitable trigonometry ratios in all triangles. Do, needed manipulations to get the desired expression given in the question.
Complete step by step solution:
Three triangles are AED , BED and CED.
Let us assume that height of the tower DE = h
Also, assume CD is x
Then distance between first station to foot of tower AD = a+x
and distance between second station to foot of tower BD = b+x
As given in the question, we know that $\alpha $, $\beta $ are the angle of elevation two stations to the top of the tower. Thus we have
$
\angle EAD = \alpha \\
\angle EBD = \beta \\
\angle ECD = \theta \\
$
In $\vartriangle $CDE ,
$\cot \theta = \dfrac{x}{h}$ …(1) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
In $\vartriangle $BDE ,
$\cot \beta = \dfrac{{x + b}}{h}$ …(2) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
Similarly in In $\vartriangle $ADE ,
$\cot \alpha = \dfrac{{x + a}}{h}$ …(2) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
From equation (1) , we have x = h cot$\theta $ , . Using this value in equation (2) and (3) , we get
$\cot \beta = \dfrac{{h\cot \theta + b}}{h}$ …(4)
And $\cot \alpha = \dfrac{{h\cot \theta + a}}{h}$ …(5)
Now by multiplying equation (4) by a on both sides we get
$a\cot \beta = a\cot \theta + \dfrac{{ba}}{h}$ …(6)
Similarly, by multiplying equation (5) by b on both sides we get
$b\cot \alpha = b\cot \theta + \dfrac{{ab}}{h}$ …(7 )
We subtract equation (6) from (7) , we get,
$
b\cot \alpha - a\cot \beta = b\cot \theta - a\cot \theta \\
\Rightarrow (b - a)\cot \theta = b\cot \alpha - a\cot \beta \\
\Rightarrow \cot \theta = \dfrac{{b\cot \alpha - a\cot \beta }}{{b - a}} \\
$
Hence we have proved the expression given in the problem.
Note:
Height and distance problems are very much solvable through the proper use of trigonometry ratios and obviously proper use of algebraic manipulations. Careful visualization of the problem and diagram will make the task easier.
First draw the diagram carefully with observation of the question. Then we can see three right angled triangles. Assume the unknown lengths with some variables. Apply suitable trigonometry ratios in all triangles. Do, needed manipulations to get the desired expression given in the question.
Complete step by step solution:
Three triangles are AED , BED and CED.
Let us assume that height of the tower DE = h
Also, assume CD is x
Then distance between first station to foot of tower AD = a+x
and distance between second station to foot of tower BD = b+x
As given in the question, we know that $\alpha $, $\beta $ are the angle of elevation two stations to the top of the tower. Thus we have
$
\angle EAD = \alpha \\
\angle EBD = \beta \\
\angle ECD = \theta \\
$
In $\vartriangle $CDE ,
$\cot \theta = \dfrac{x}{h}$ …(1) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
In $\vartriangle $BDE ,
$\cot \beta = \dfrac{{x + b}}{h}$ …(2) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
Similarly in In $\vartriangle $ADE ,
$\cot \alpha = \dfrac{{x + a}}{h}$ …(2) ( as cot ratio = $\dfrac{{base}}{{perpendicular}}$ )
From equation (1) , we have x = h cot$\theta $ , . Using this value in equation (2) and (3) , we get
$\cot \beta = \dfrac{{h\cot \theta + b}}{h}$ …(4)
And $\cot \alpha = \dfrac{{h\cot \theta + a}}{h}$ …(5)
Now by multiplying equation (4) by a on both sides we get
$a\cot \beta = a\cot \theta + \dfrac{{ba}}{h}$ …(6)
Similarly, by multiplying equation (5) by b on both sides we get
$b\cot \alpha = b\cot \theta + \dfrac{{ab}}{h}$ …(7 )
We subtract equation (6) from (7) , we get,
$
b\cot \alpha - a\cot \beta = b\cot \theta - a\cot \theta \\
\Rightarrow (b - a)\cot \theta = b\cot \alpha - a\cot \beta \\
\Rightarrow \cot \theta = \dfrac{{b\cot \alpha - a\cot \beta }}{{b - a}} \\
$
Hence we have proved the expression given in the problem.
Note:
Height and distance problems are very much solvable through the proper use of trigonometry ratios and obviously proper use of algebraic manipulations. Careful visualization of the problem and diagram will make the task easier.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE